The fellowship of the ring - Tolkien, J. R. R. (HarperCollins London, 2012)
The 'Fellowship of the Ring' is the first part of Tolkien's epic adventure 'The Lord of the Rings'. Frodo Baggins finds himself faced with an immense task, as his elderly cousin Bilbo entrusts the Ring to his care